The dynamics of uncertainty, macroeconomic variables, and capital market performance: A case study of Nigeria - Emmanuel Ayeni; Oluwaseyi Fanibuyan (Research in Globalization, 2022)
Economic uncertainty is gradually spreading across the globe due to government intervention and global development. Though it has been extensively shown in the literature that uncertainty impacts every economic sector, various economic agents also respond to uncertainty differently, particularly when faced with an unexpected shock. Thus, this study explores the interrelationship between uncertainty, macroeconomic variables, and capital market performance in Nigeria. Findings show that uncertainty has no impact on the macroeconomic performance of Nigeria. However, the prices of crude oil impact macroeconomic performance in the country as it has a positive and significant impact on the gross domestic product, all-share index, and money supply of the Nigerian economy. The economy is exposed to external uncertainty from crude oil exports which trigger domestic uncertainty leading to macroeconomic instability in Nigeria. The study thereby recommended that a framework be developed in the Nigerian economy to reduce the domestic economy from external shock because the internal shock was found to be insignificant.
Keywords: 330; Uncertainty; All share index; Economy performance; Gross domestic product; Money supply